Senecio eliseae (Compositae, Senecioneae), a new species from the southern Ecuadorian Andes - Calvo, Joel (Phytotaxa, 2015)
Senecio eliseae is described as a new species from the southern Ecuadorian Andes. It is a suffrutescent herb characterized by erect branches that are leaved only in the upper half, yellow discoid nodding capitula, and glandular-hirsute indumentum on the stem, leaves, and synflorescence. Detailed photographs of plants from the type locality are provided.